2020
DOI: 10.1016/j.ajur.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of androgen receptor variants in prostate cancer

Abstract: Aberrant activation of androgen receptor (AR) signaling occurs in patients treated with AR-targeted therapies, contributing to the development of castration-resistant prostate cancer (CRPC) and therapeutic resistance. Over the past decade, many AR variants (AR-Vs) have been identified in prostate cancer cell lines and clinical CRPC specimens. These AR-Vs lack the COOH-terminal ligand-binding domain (LBD), and may mediate constitutively active AR signaling acquired following AR-targeting therapies. AR splice va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Among the 23 isoforms, only the full-length one (AR-FL) and the AR-V7 variant, which lack the hinge and E/F domains but have a short C-terminal specific sequence, are mentioned because of their involvement in gliomagenesis. Adapted from [99]. (D): GR isoforms are encoded by the GR gene through alternative splicing of exons 9α/9β, giving rise to GRα or GRβ proteins, respectively, or use of different translational initiation sites that produce multiple GRα isoforms termed A through D (A, B, C1-C3 and D1-D3).…”
Section: Estrogen Receptors Complex and Interconnected Signaling Patmentioning
confidence: 99%
“…Among the 23 isoforms, only the full-length one (AR-FL) and the AR-V7 variant, which lack the hinge and E/F domains but have a short C-terminal specific sequence, are mentioned because of their involvement in gliomagenesis. Adapted from [99]. (D): GR isoforms are encoded by the GR gene through alternative splicing of exons 9α/9β, giving rise to GRα or GRβ proteins, respectively, or use of different translational initiation sites that produce multiple GRα isoforms termed A through D (A, B, C1-C3 and D1-D3).…”
Section: Estrogen Receptors Complex and Interconnected Signaling Patmentioning
confidence: 99%
“…AR DNA sequencing has revealed that intricate AR genomic arrangements are occurring in CRPC specimens, some of which are associated with AR-V expression [8]. Further study is needed to determine a causal relationship between each rearrangement and the expression of AR-Vs. To summarize, AR-Vs generated either by intragenic rearrangements or aberrant RNA splicing show varying degrees of transcriptional activity and some of them, especially constitutive active AR-Vs such as AR-V7, are likely the result of altered hormonal environment where canonical AR-FL signaling is suppressed as well as the permissive genomic and epigenomic features acquired in the development of CRPC, as we elaborated in a recent review [9].…”
Section: Structure Of Ar-vs and Mechanisms Underlying Genesis Of Ar-vsmentioning
confidence: 96%
“…Although many AR-Vs (including AR-V7) lack exon 4, encoding a part of NLS, they may still enter the nucleus and activate transcription to varying degrees independent of the canonical AR NLS and in the absence of AR-FL, possibly due to the NLS-like basic amino acid sequences downstream of AR DBD [1,5]. AR-Vs can be categorized into the following four groups depending on their nuclear localization ability: ligand stimulated in a similar manner to canonical AR-FL (e.g., AR-23), constitutively active (e.g., AR-V3, 4, 7, 12), conditionally active (e.g., AR45, AR-V1, 9), and inactive (e.g., AR-V13, 14, AR8) [4]. AR-Vs reported in other studies but yet to be fully characterized [6,7], and those arising from diverse AR gene rearrangements [8], are not included in Figure 1.…”
Section: Structure Of Ar-vs and Mechanisms Underlying Genesis Of Ar-vsmentioning
confidence: 99%
“…The findings from studies focusing on splicing factors and related regulators are summarized in Figure 2 . Readers are directed to a recent review 70 for further reading on the specific topic of AR-V regulation, the role of genomic structural alterations, and the requirement of low androgens for AR-V7 generation.…”
Section: Molecular Origin and Regulation Of Ar-v Expressionmentioning
confidence: 99%
“…(A) AR gene structure with canonical and cryptic exon splice junctions marked according to GRCh37/hg19 human genome sequences (not drawn to scale); (B) Nomenclature, functional annotation, exon compositions, and variant-specific mRNA (color matched to Figure 1A) and peptide sequences (in gray). Modified from reference # 70 .…”
Section: Figurementioning
confidence: 99%